Effect of Gross Domestic Product and Interest Rate on Tax Revenue in Indonesia - Anizir Ali Murad; Deviyantoro Deviyantoro; Kamaluddin Kamaluddin; Dedik Wiryawan; Efriyani Sumastuti (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Taxes play an important role in the life of the state, especially in the implementation of development because the revenue in the tax sector can finance the development expenditure of a country. This study aims to determine and analyze the effect of gross domestic product and interest rate on tax revenue in Indonesia. In this study, data from 1990 to 2020 were used which were obtained from various sources. This study uses a multiple linear regression model with the least squares method with the Eviews 7 application. The results show that gross domestic product has significant effect on tax revenue in Indonesia. Interest rate has significant effect on tax revenue in Indonesia.